2005
DOI: 10.1073/pnas.0501447102
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and molecular properties of pheromone binding and release

Abstract: Transient kinetic studies have shown that the uptake of the pheromone (bombykol) of the silkworm moth (Bombyx mori), by its pheromone-binding protein (PBP) BmorPBP, proceeds with an ''on'' rate of 0.068 ؎ 0.01 M ؊1 ⅐s ؊1 . With the high concentration of PBP in the sensillar lymph (10 mM), the half-life for the uptake of pheromone in vivo is Ϸ1 ms. A pH-dependent conformational change (BmorPBP B 3 BmorPBP A ), associated with the release of pheromone, is a first-order reaction (k ‫؍‬ 74.1 ؎ 0.32 s ؊1 ; t1/2, 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
3
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 30 publications
6
141
3
3
Order By: Relevance
“…At a pH lower than 5.5, the C terminus of BmorPBP adopts a newly formed α-helix conformation occupying the bombykol-binding site, whereas at a pH higher than 5.5, the same C-terminus region forms an elongated stretch outside the binding site, making it available for the pheromone. These results led the authors to propose a pH-induced ligand-releasing mechanism, through which BmorPBP ejects the bound pheromone to its receptor when encountering the low pH generated by the negatively charged membrane surfaces (15,(18)(19)(20)(21)(22). A similar ligand-releasing mechanism is observed for a PBP from the giant silk moth Antheraea polyphemus (14,23).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…At a pH lower than 5.5, the C terminus of BmorPBP adopts a newly formed α-helix conformation occupying the bombykol-binding site, whereas at a pH higher than 5.5, the same C-terminus region forms an elongated stretch outside the binding site, making it available for the pheromone. These results led the authors to propose a pH-induced ligand-releasing mechanism, through which BmorPBP ejects the bound pheromone to its receptor when encountering the low pH generated by the negatively charged membrane surfaces (15,(18)(19)(20)(21)(22). A similar ligand-releasing mechanism is observed for a PBP from the giant silk moth Antheraea polyphemus (14,23).…”
mentioning
confidence: 73%
“…Octanal, nonanal, decanal, and geranylacetone showed significant binding affinity, but γ-octalactone did not bind. and quantified by gas chromatography according to a previously reported "cold-binding assay" (20). Additionally, binding was measured by a competitive binding assay using N-phenyl-1-naphthylamine as a fluorescent reporter (47).…”
Section: Methodsmentioning
confidence: 99%
“…OBP is able to bind its ligand at neutral pH and to eject it in a very fast process (t 1/2 = 9 ms) in low pH condition localized on adjacent negatively charged olfactory receptor neuron (28,29). Our binding assay showed that CjapNPC2 bound to a wide variety of long-chain fatty acids, alcohols, and acetates at neutral pH and dissociated with these ligands at low pH.…”
Section: Cjapnpc2 Carries Hydrophobic Semiochemicals Evoking Antennalmentioning
confidence: 91%
“…Growing evidence supports that odorant binding proteins (OBP) and chemosensory proteins (CSP) are involved in solubilizing and transporting odorants and pheromones through aqueous hemolymph in insects (Leal et al, 2005;Ozaki et al, 2005). The chemical messages carried by the OBPs and CSPs are decoded when odorant receptors (OR) or in some cases gustatory receptors (GR) selectively bind different chemicals (Vosshall and Stocker, 2007).…”
Section: Introductionmentioning
confidence: 99%